A toddler diagnosed with severe postinfectious bronchiolitis obliterans and COVID‐19 infection. Issue 7 (4th May 2021) - Koletsi, Patra; Antoniadi, Marita; Mermiri, Despina; Koltsida, Georgia; Koukou, Dimitra; Noni, Maria; Spoulou, Vasiliki; Michos, Athanasios
Abstract: During the COVID‐19 pandemic, management of SARS‐CoV‐2 infection in children with underlying chronic lung disease has been challenging. There are limited studies in children with respiratory comorbidities, apart from asthma, presumably due to low morbidity of SARS‐CoV‐2 infection in the general pediatric population along with the low incidence of certain pulmonary conditions. Compassionate use of remdesivir has been shown to reduce time to clinical improvement in adults and has been retrospectively studied in small pediatric cohorts with promising results. Whether children with underlying respiratory conditions may benefit from antiviral treatment in the context of different pathophysiologic backgrounds and unknown drug safety and efficacy needs to be further evaluated. We present a case of COVID‐19 infection in a 3‐year old toddler with severe postinfectious bronchiolitis obliterans, who received compassionate treatment with 5‐day‐course of remdesivir, and recovered with favourable outcome.